Effect of an intervention in Physical Education classes on health related levels of physical fitness in youth - Oliveira, Luciane; Braga, Fernando; Lemes, Vanilson; Dias, Arieli; Brand, Caroline; Mello, Júlio; Gaya, Anelise; Gaya, Adroaldo (Revista Brasileira de Atividade Física & Saúde, 2017)
The aim of this study was to verify the effect of an intervention program during Physical Education (PE) classes on levels of physical fitness related to health in youth. This is a pre-experimental study. The students (40 boys and 48 girls) were conveniently selected from a private school in Southern Brazil. Cardiorespiratory fitness was assessed through the six-minute test, recorded in meters (m), flexibility through the sit-and-reach test, recorded in centimeters (cm), abdominal strength/resistance through repetitions in one minute (rep) and body mass index (BMI) through the [mass/height²] equation. The intervention program was conducted in PE classes, often twice a week, during an entire school year. Data analysis was performed using descriptive analysis, Student’s t-test and repeated measures ANOVA, taking into consideration p<0.05. The PE program promoted improvement in cardiorespiratory fitness for boys (pre-test: 1123.0m±197.0m; post-test: 1247.2m±139.6m; p=0.002) and girls (pre-test: 940.7m±75.0m; post-test: 1028.7m±67.3m; p=0.001); abdominal strength/resistance for boys (pre-test: 46.15rep±10.15rep; post-test: 53.90rep±10.49rep; p=0.001) and girls (pre-test: 36.39rep±8.32rep; post-test: 44.00rep±6.16rep; p=0.001); and flexibility for boys (pre-test:22.77cm±8.11cm; post-test: 27.60cm±7.23cm; p=0.006) and girls (pre-test: 32.08cm±6.21cm; post-test: 34.89cm±6.43cm; p=0.032). There weren’t changes in mean BMI values. Therefore, it’s considered that the PE program aimed at health promotion through physical fitness can improve the indicators of cardiometabolic and muscle-skeletal health in students.